Monitoring of non-linear ground movement in an open pit iron mine based on an integration of advanced DInSAR techniques using TerraSAR-X data - Mura, José Claudio; Paradella, Waldir R.; Gama, Fabio F.; Silva, Guilherme G.; Galo, Mauricio [UNESP]; Camargo, Paulo O. [UNESP]; Silva, Arnaldo Q.; Silva, Aristotelina (MDPI, 2016)
This work presents an investigation to determine ground deformation based on an integration of DInSAR Time-Series (DTS) and Persistent Scatterer Interferometry (PSI) techniques aiming at detecting high rates of linear and non-linear ground movement. The combined techniques were applied in an open pit iron mine located in Carajás Mineral Province (Brazilian Amazon region), using a set of 33 TerraSAR-X-1 images acquired from March 2012 to April 2013 when, due to a different deformation behavior during the dry and wet seasons in the Amazon region, a non-linear deformation was detected. The DTS analysis was performed on a stack of multi-look unwrapped interferograms using an extension of the SVD (Singular Value Decomposition), where a set of additional weighted constraints on the acceleration of the displacement was incorporated to control the smoothness of the time-series solutions, whose objective was to correct the atmospheric phase artifacts. The height errors and the deformation history provided by the DTS technique were used as previous information to perform the PSI analysis. This procedure improved the capability of the PSI technique to detect non-linear movement as well as to increase the numbers of point density of the final results. The results of the combined techniques are presented and compared with total station/prisms and ground-based radar (GBR) measurements.
Keywords: DInSAR time-series; Open pit iron mine; PSI; Surface movement